Partial loss‐of‐function variant in neuregulin 1 identified in family with heritable peripheral neuropathy. Issue 9 (17th May 2022) - Lysko, Daniel E.; Meireles, Ana M.; Folland, Chiara; McNamara, Elyshia; Laing, Nigel G.; Lamont, Phillipa J.; Ravenscroft, Gianina; Talbot, William S.
Abstract: Neuregulin 1 signals are essential for the development and function of Schwann cells, which form the myelin sheath on peripheral axons. Disruption of myelin in the peripheral nervous system can lead to peripheral neuropathy, which is characterized by reduced axonal conduction velocity and sensorimotor deficits. Charcot‐Marie‐Tooth disease is a group of heritable peripheral neuropathies that may be caused by variants in nearly 100 genes. Despite the evidence that Neuregulin 1 is essential for many aspects of Schwann cell development, previous studies have not reported variants in the neuregulin 1 gene ( NRG1 ) in patients with peripheral neuropathy. We have identified a rare missense variant in NRG1 that is homozygous in a patient with sensory and motor deficits consistent with mixed axonal and de‐myelinating peripheral neuropathy. Our in vivo functional studies in zebrafish indicate that the patient variant partially reduces NRG1 function. This study tentatively suggests that variants at the NRG1 locus may cause peripheral neuropathy and that NRG1 should be investigated in families with peripheral neuropathy of unknown cause.